(untitled) (Research, Society and Development, 2022)
During the Covid-19 pandemic, there was an increase in the commercial consumption of the medicines Hydroxychloroquine and Ivermectin for the treatment of the disease due to the positive results found in in vitro tests. However, there is no scientific evidence that these drugs, in safe dosages, are effective for the pathology in humans. In this sense, this study aimed to evaluate the toxicity and genotoxicity of drugs through the Allium cepa bioassay. Thus, for the positive control, 800mg of Paracetamol was used and for the negative control, treated water. The drugs Hydroxychloroquine and Ivermectin showed toxic potential at their usual dosages. In addition, one of the bulbs treated with Ivermectin showed morphological changes in its roots. The antimalarial drug (Hydroxychloroquine) did not present a genotoxic risk at the dosages tested, but it poses a risk to human health when administered in excess, without medical advice, or in association with other drugs, such as azithromycin. The drug Ivermectin presented a genotoxic risk in two of the four concentrations tested, showing an increase in the number of micronuclei according to the increase in the dose. Therefore, for the consumption of these drugs, responsible medical monitoring is necessary, in addition to following the appropriate recommendations. To date, the correct vaccination protocol is the only effective method of prophylaxis.